Possibilities of Habit-Change in The Essex Serpent: A Semiotic Analysis of Cora Seaborne - Onur Eyüp Böle (Ideas: Journal of English Literary Studies)
This article offers a semiotic approach to Sarah Perry’s 2016 novel The Essex Serpent. In the light of Teresa de Lauretis’s study of interpretants in relation to female subjectivity, it becomes evident that Perry in her protagonist Cora Seaborne reformulates female experience as an active and immanent force in socio-cultural processes of semiotic production. This article analyses this force in terms of de Lauretis’s habit-change, which defines subjectivity as a nexus between the norms that produce it and the change on which the very possibility of semiotic production depends. The full development of Perry’s protagonist in these terms brings about an awareness about this in-betweenness, which produces a non-binary and non-hierarchical ethical turn beyond rigid categories that define the subject’s relationship with the world. This ethical turn, this article demonstrates, is specifically important in that it situates female subjectivity inside history instead of marginalising it in an exclusive or antithetical manner, and that it offers a liberating space for all its participants (including the Victorian male characters).